2015
DOI: 10.1093/jmcb/mjv016
|View full text |Cite
|
Sign up to set email alerts
|

Efficient inversions and duplications of mammalian regulatory DNA elements and gene clusters by CRISPR/Cas9

Abstract: The human genome contains millions of DNA regulatory elements and a large number of gene clusters, most of which have not been tested experimentally. The clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated nuclease 9 (Cas9) programed with a synthetic single-guide RNA (sgRNA) emerges as a method for genome editing in virtually any organisms. Here we report that targeted DNA fragment inversions and duplications could easily be achieved in human and mouse genomes by CRISPR with tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
140
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(148 citation statements)
references
References 105 publications
(164 reference statements)
7
140
1
Order By: Relevance
“…Three studies of Cas9-injected mouse zygotes explicitly suggest that MMEJ is responsible for repair, rather than C-NHEJ (Li et al, 2015; Yang et al, 2013; Yasue et al, 2014), because the same alleles were repeatedly recovered in independently derived mice and repaired alleles appeared to utilize microhomologous repeat sequences. We also found that the alleles in Cas9-injected rats (Shao et al, 2014) and monkeys (Niu et al, 2014) have the sequence features expected from microhomology-mediated repair.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies of Cas9-injected mouse zygotes explicitly suggest that MMEJ is responsible for repair, rather than C-NHEJ (Li et al, 2015; Yang et al, 2013; Yasue et al, 2014), because the same alleles were repeatedly recovered in independently derived mice and repaired alleles appeared to utilize microhomologous repeat sequences. We also found that the alleles in Cas9-injected rats (Shao et al, 2014) and monkeys (Niu et al, 2014) have the sequence features expected from microhomology-mediated repair.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the last year, several enhancers have been deleted in mice using 2c CRISPR including those associated with expression of Bcl11a , 94 Blimp1 , 95 Mef2c , 96 Stat5 , 97 Pcdh , 98 Mmp13, 99 Gata3 , 100 and Cebpa . 101 In each case, deletion of the enhancer compromised expression of the associated target gene.…”
Section: Two-component Crisprmentioning
confidence: 99%
“…47,48,58 Introduction of 2 engineered nucleases can result in targeted deletion or inversion, duplication, local indels at nuclease cleavage sites, or translocations/ chromosomal rearrangements. [60][61][62][63][64][65][66][67][68][69][70][71][72][73] Here, we review genome-editing approaches for genetic correction and disruption strategies for the b-hemoglobinopathies as summarized in Figure 1 and Table 1.…”
Section: Introductionmentioning
confidence: 99%